Впровадження деяких спеціальних технологій інклюзивного навчання математики учнів з синдромом дефіциту уваги та гіперактивністю - Яценко, Світлана (Дидактика математики: теорія, досвід, інновації, 2024)
The article demonstrates the possibilities of using cooperative learning and fairy-tale therapy as separate technologies for teaching mathematics for students with special educational needs who have attention deficit hyperactivity disorder. Such technologies as corporate training, fairy-tale therapy contribute to the development of confidence in the abilities of students with SEN, since in small groups all students must be active as listeners and speakers. For them, the behavior of classmates becomes a good example of an equal and friendly attitude towards everyone in the group. As a result, in addition to the positive socialization that all students need, the level of interest in acquiring knowledge increases in students with SEN. Storytelling adds emotional richness to the lesson and contributes to a positive attitude towards learning new material in mathematics. A child with ADHD can feel like the hero of a fairy tale-task and therefore more willingly undertakes to solve them. With these technologies, a child with ADHD participates more actively in learning mathematics, feels like an integral part of the class. Cooperative learning and storytelling become tools for increasing interest in mathematics. The research results were obtained through the use of empirical (experiment, observation, description) and theoretical (analysis, generalization, induction) methods. The proposed methodology demonstrates ways of implementing the ideas of inclusive education in the educational space. В статті продемонстровано можливості використання кооперативного навчання та казкотерапії, як окремих технологій навчання математики для учнів з особливими освітніми потребами, які мають синдром дефіциту уваги з гіперактивністю. Такі технології як корпоративне навчання, казкотерапія сприяють розвитку впевненості в своїх можливостях учнів з ООП, оскільки в малих групах усі учні мають бути активними як слухачами так і доповідачами. Для них поведінка однокласників стає гарним прикладом рівноправного дружнього ставлення до кожного в групі. Як наслідок, окрім позитивної соціалізації яка потрібна всім учням, в учні з ООП підвищується рівень зацікавленості до здобуття знань. Казкотерапія додає емоційного насичення уроку та сприяє позитивному налаштування на вивчення нового матеріалу з математики. Дитина з СДУГ може відчувати себе героєм казки-задачі і тому з більшою охотою береться за їх розв’язання. З цими технологіями дитина з СДУГ активніше бере участь у навчанні математики, відчуває себе невід’ємною частиною класу. Кооперативне навчання та казкотерапія стають інструментами підвищення інтересу до математики. Результати дослідження отримані за рахунок використання емпіричних (експеримент, спостереження, опис) та теоретичних (аналіз, узагальнення, індукція) методів. Пропонована методика демонструє шляхи реалізації ідей інклюзивної освіти в навчальний простір.